Researchers and practitioners talk about users and each other: making user and audience studies matter - Brenda Dervin; CarrieLynn Reinhard (Information Research: An International Electronic Journal)
Introduction. We report here on the research phase of a multi-stage dialogue examining convergences and divergences in how three fields (library and information science, human computer interaction and communication and media studies) looked at users and each other. Focus was on what researchers and practitioners saw as the big unanswered questions in user studies and what they saw as the convergences and divergences across disciplinary and practice-research divides. Method. Eighty-three international experts in the three fields were interviewed by phone; thirty-one local experts, public and academic librarians serving universities and colleges in central Ohio, were interviewed using self-journals and focus group reports. Analysis. A thematic analysis was completed. Purpose was not to fix substantive differences but to tap ways in which convergences and divergences showed relevance to the communicative aspects of the research enterprise. A theory of dialogue was applied that purposively positioned this analysis as only one of potentially many. Results. All informants showed strong commitment to improving user studies and making them matter more to design, practice and society. At the same time, regardless of field or perspective, they struggled with the incoherencies of avalanches of user research. They decried the general inability to communicate across fields and between research and practice. They decried the ways in which structural conditions seemed to constrain possibilities. Yet, they hoped for making things better. Conclusion. . The traditional modes used for communication in the social science research enterprise are not doing the job for user studies. We need to reclaim some procedures lost in the current emphases on quantity over quality and invent other options. This is the theme of our second paper, in this same issue.